2015
DOI: 10.1038/ijir.2015.1
|View full text |Cite
|
Sign up to set email alerts
|

The association between plasma visfatin levels and ED

Abstract: Visfatin was initially proposed as a clinical marker of atherosclerosis, endothelial dysfunction and vascular damage, with a potential prognostic value. It has been shown that endothelial dysfunction has an important role in ED. We aimed to determine the levels of visfatin in ED patients and characterize the relationship between visfatin levels and ED. This case-control study was conducted between October 2010 and August 2012, and 41 severe ED patients (group 1) and 36 healthy controls (group 2) were involved.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Recently, Villalobos et al further investigated the detrimental effects of visfatin on ECs and showed that visfatin-induced ROS production causes DNA destruction, p53 upregulation, and telomere dysfunction in HUVECs [306]. Nevertheless, recent study by Karataş et al showed no such association between visfatin serum levels and ED [307].…”
Section: Visfatinmentioning
confidence: 91%
“…Recently, Villalobos et al further investigated the detrimental effects of visfatin on ECs and showed that visfatin-induced ROS production causes DNA destruction, p53 upregulation, and telomere dysfunction in HUVECs [306]. Nevertheless, recent study by Karataş et al showed no such association between visfatin serum levels and ED [307].…”
Section: Visfatinmentioning
confidence: 91%